PELABELAN TOTAL SISI AJAIB SUPER (TSAS) PADA GABUNGAN GRAF ULAT BULU DAN BIPARTITE LENGKAP - Sudarsana, I Wayan; Fitria, Fitria; Musdalifah, Selvy (Natural Science: Journal of Science and Technology, 2014)
An  edge anti-magic total labelling, -EAMT, on graph  with  vertices and  edges is bijektion , which has a set of edge weights  with  and . A  super edge anti-magic total labelling , -SEAMT, if the vertex set of  obtain the smallest labels . An -EAMT (SEAMT) labelling  is called EMT (SEMT) labelling if  and . Furthermore,  is called the magic constant. A graph  is said EMT, SEMT, -EAMT and -SEAMT if there is EMT, SEMT, -EAMT and -SEAMT labelling on graph , respectively. In this paper, we showed that the union of caterpillars and complete bipartite graph are SEAMT and SEMT, especialy for  has (-SEAMT and -SEAMT with ; graph  has -SEAMT and -SEAMT for ; and graph  has -SEAMT and -SEAMT with       where  and  for . Thus, graph  is SEMT with  for ; graph  also SEMT with  for ; as well graph  is SEMT with  for .